Intellectual capital disclosure in companies listed in the Kuala Lumpur Stock Exchange (KLSE) in 2002 / Gan Kin and Rajasegaran Krishnasamy - Gan, Kin; Rajasegaran Krishnasamy (Institute of Research, Development and Commercialization (IRDC), 2004)
The ascendancy of the knowledge based economy has placed great importance on the Intellectual Capital (IC) possessed by organizations. IC has now become a significant factor of production, sidestepping the traditional factors of production, namely land, labour and capital. It has now become the key factor in determining whether or not organizations gain competitive advantage. In the traditional reporting methods, tangible assets that were the engine of growth of the industrial economy, were profound. This traditional reporting, however does not deliver much of the information that stakeholders now use to assess company performance. The findings from this project show that IC disclosure by companies listed in the KLSE is still at a premature stage, only 28.3% of the sample chosen disclosed IC related terms. The most popular terms that were found disclosed in this study were employee skill, management quality, information systems, employee knowledge and employee productivity. Also the disclosure of IC related terms did not co-relate with company size.